Mapping 45S and 5S ribosomal genes in chromosomes of Anostomidae fish species (Ostariophysi, Characiformes) from different Amazonian water types - Barros, Lucas Caetano de; Galetti Jr., Pedro M.; Feldberg, Eliana (Hydrobiologia, 2017)
The fish from the family Anostomidae represent one of the most important groups of freshwater ichthyofauna from South America, with species of high economical value. The migratory characteristic of some species, through the several Amazonian environments, takes them into waters with different physico-chemical characteristics. Cytogenetic studies on the Anostomidae demonstrate that these fishes have a conserved diploid number and karyotype macrostructure. So, to verify if this conservation occurs also in the genomic level, the current study aimed at a chromosomal comparative physical mapping, using 45S and 5S rDNA, of seven species of anostomids: Leporinus fasciatus, L. agassizi, L. friderici, L. trifasciatus, Rhytiodus macrolepis, Laemolyta taeniata, and Schizodon fasciatus, collected in different Amazonian environments. The results obtained corroborate the conservation of the karyotype macrostructure. However, significant differences were found in the distribution of heterochromatin and on the pair bearing the nucleolus organizer region. The staining of 45S and 5S rDNA by FISH highlighted, for four of the seven species, more than one chromosome pair bearing the site 45S. The 5S rDNA, although present in only one chromosome pair, varied in its chromosome and karyotype position. Thus, although the Anostomidae family has a conserved chromosomic macrostructure the use of molecular techniques revealed the presence of chromosomic translocation during the evolution of these fishes. © 2016, Springer International Publishing Switzerland.
Keywords: Chromosome; Cytogenetics; Freshwater Environment; Gene Expression; Genomics; Karyotype; Physicochemical Property; Teleost; South America; Anostomidae; Characiformes; Leporinus Fasciatus; Ostariophysi; Pisces